A thermoplastic polyurethane/rare earth composite film with adjustable fluorescence colors and optimal low‐temperature flexibility. Issue 1 (11th August 2022) - Zhu, Rongli; Pu, Zejun; Wang, Xu; Hou, Hongbo; Li, Xianyong; Zhong, Jiachun
Abstract: In this study, a unique series of luminous polymeric rare earth (RE) composite films was produced by loading RE ions into thermoplastic polyurethane (TPU) using solution blending. Compared to RE ions, luminous polymeric RE composites had greater luminescence intensity, indicating that the introduction of polymer polyurethane as the polymer matrix was advantageous for the luminescence intensity and efficiency of RE ions, with the polymer matrix's absorbed energy being transferred to the RE ions. Furthermore, the findings of the optical transmittance, UV–visible absorption and fluorescence emission spectra suggest that TPU‐RE composite films possess exceptional fluorescence luminescence properties and optical transparency. Surprisingly, the fluorescence colors of TPU‐RE fluorescent films could be adjusted between red and green by varying the ratios of Eu 3+ and Tb 3+ in the films and can be any mixture of red and green hues. In addition, the temperature at 5% weight loss ( T 5% ) for the TPU‐RE composite film composition reached 250 °C. In addition, pure TPU and all TPU‐RE hybrid films demonstrated a glass transition temperature ( T g ) of about −30 °C. Simultaneously, the tensile strength of the TPU‐T0 E10 film reached its maximum (43.6 MPa). Consequently, the TPU‐RE composite films will be utilized as photoluminescent functional materials. © 2022 Society of Industrial Chemistry. Abstract : The fluorescence colors of TPU‐RE films may be changed between red and green by modifying the ratios of Eu 3+ and Tb 3+ in the films.